Selective regulation of 14-3-3η in primary culture of cerebral cortical neurons and astrocytes during development - Chen, Xiao Qian; Liu, Shuang; Qin, Lu Ye; Wang, Chen Ran; Fung, Yin-Wan Wendy; Yu, Albert Cheung-Hoi (Journal of neuroscience research, 2005)
The 14‐3‐3 proteins exist predominantly in the brain and may play regulatory roles in cellular processes of growth, differentiation, survival, and apoptosis. The biological functions, however, of the various 14‐3‐3 isoforms (β, ϵ, η, γ, and ζ) in the brain remain unclear. We have reported previously upregulation of 14‐3‐3γ in ischemic astrocytes. In the present study, we report selective regulation of 14‐3‐3η in cultured cerebral cortical neurons and astrocytes during in vitro development. In cultured neurons, gene expression levels of 14‐3‐3η increase with culture age (0–10 days). Brain‐derived neurotrophic factor and neurotrophin‐3 upregulate 14‐3‐3η gene expression. In cultured astrocytes, 14‐3‐3η is downregulated with culture age (1–5 weeks). The gene expression level of 14‐3‐3η is not affected by scratch injury in astrocytes or by ischemia in neurons. These data suggest a possible role of 14‐3‐3η in growth and differentiation of neurons and astrocytes, indicating an intricate mechanism governing coordinated and well‐controlled developmental events in the brain to ensure normal neural functions. © 2004 Wiley‐Liss, Inc.